Target classification scheme using phase characteristics for automotive FMCW radar. Issue 25 (1st December 2016) - Lee, Jingu; Kim, Daehyun; Jeong, Seonghee; Ahn, Gil‐Cho; Kim, Younglok
Abstract : Moving target has a non‐coherent phase characteristic regardless of micro‐Doppler effect caused by body motion, because the movement of the target changes the beat‐frequency and its phase. A phase compensation method to remove the phase variations caused by movement is proposed. Using the proposed phase compensation method, it is possible to classify targets as pedestrians or automobiles based on the phase variance because pedestrians and automobiles have non‐coherent and coherent phases, respectively. Through applying experimental data, the possibility of target classification is shown.